CERTAIN STRUCTURAL CHARACTERISTICS OF DENTISHION SMALL DEFECTS IN THE ADULT POPULATION OF KHARKIV - Slynko, Yu.O.; Sokolova, I.I.; Udovychenko, N.M.; Oleynichuk, V.V. (World of Medicine and Biology, 2020)
The article presents data obtained from the orthopantomogram analysis of 1269 patients aged 18 to 84 years of both genders for such a structural feature of the dental arches’ small defects as their length (absence of one, two or three teeth). It was found that the maximum number of defects was with the absence of one tooth (1265 defects, 66.1 %), and the smallest share of defects was the length of three teeth (149 дефектів, 7.8 %). There is a direct correlation between the examined persons’ age increase and the number of simultaneous presence of two, three, four, five and even six small defects of the dental arches with the absence of one to three teeth. Also, when analyzing the structure of the dentition small defects, which had different lengths, no significant gender-based differences were found.
Keywords: dentitions; partial secondary adentia; small dentition defects; structure